PSYCHOLOGICAL BASICS OF GAMIFIED LEARNING THEORY - Rustamjonova, Mukharramkhon (INTERNATIONAL CONFERENCES, 2023)
The article reveals the features of psychological concept of gamification will be reconsidered, using numerous motivational ways and a plethora of concerns.